1973
DOI: 10.1111/j.1365-2621.1973.tb01705.x
|View full text |Cite
|
Sign up to set email alerts
|

The hydrolysis of sodium triphosphate in cod and beef muscle

Abstract: Polyphosphates can be used in meat and fish products to reduce liquor loss during processing. However, there have been indications that triphosphate and pyrophosphate are hydrolysed in muscle. This effect has been studied in cod and beef using P32 labelled triphosphate and it is found that the kinetics conform to a typical 'consecutivey reaction of the type For cod, k, 21 k2 and only orthophosphate remains after 30-40 hr at 0°C.In beef k, 4 k,, and also k, (beef) < k , (cod). This results in higher levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 2 publications
(1 reference statement)
1
17
0
Order By: Relevance
“…pH is very important for WHC as it affects protein conformation (Bertram and others 2004b; Martinez‐Alvarez and Gomez‐Guillen 2006). Furthermore, it may affect enzyme (phosphatase) activity (Sutton 1973). The pH values of the brines used ranged from 5.83 (hexametaphosphate with salt) to 10.22 (basic diphosphate).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…pH is very important for WHC as it affects protein conformation (Bertram and others 2004b; Martinez‐Alvarez and Gomez‐Guillen 2006). Furthermore, it may affect enzyme (phosphatase) activity (Sutton 1973). The pH values of the brines used ranged from 5.83 (hexametaphosphate with salt) to 10.22 (basic diphosphate).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the prime objective was economical and increased quality (that is, texture and flavor improvement) was a positive side effect. Studies have indicated that phosphates can be decomposed prior to freezing of cod (Sutton 1973). This study complements available findings indicating that the positive effect of triphosphate was maintained during processing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on TPP hydrolysis in meat systems show a wide range of time for complete hydrolysis being anywhere from 15 min for ground beef (Hamm & Neraal, 1977a) and salted ground chicken (Belton, Packer, & Southon, 1987), less than 50 min. in salted chicken breast (Li et al, 2001) and up to 16 h for beef (Sutton, 1973). At the extreme case, myosin easily has the capacity to be the major TPPase in meat, while in the most rapid case, other enzymes may be involved and/or the TPPase of myosin may be activated by actin and/or other factors in the meat system.…”
Section: Discussionmentioning
confidence: 99%
“…The likely reaction scheme for TPP metabolism in meat is (adapted from Sutton, 1973; Weilmeier & Regenstein, 2004): where k 1 involves TPP hydrolysis by tripolyphosphatase (TPPase) and k 2 involves hydrolysis by pyrophosphatase. The enzymes and the kinetics involved in TPP and PPi hydrolysis in meat systems are partially understood.…”
Section: Introductionmentioning
confidence: 99%